"For People Who Aren't Sure Who They Are, Theatre is a Great Place to Be: Narratives of Actors and their Sexual Identities - Theodore McCadden (Adult Education Research Conference, 2015)
: This narrative study of male actors who identify as other-than-heterosexual explores the participants' stories of sexual identity development and the relationship between acting and identity development. Framed in D'Augelli's (1994) lifespan developmental model, the study illustrates themes of acting as safe space, acting as an embodied experience, acting as an influence on relationships, and acting as a politic.